Cyber resiliency with IBM Storage Sentinel and IBM Storage Safeguarded Copy - Boyacioglu, Nezih; Franke, Gerd; Gerisch, Thomas; Green, David; Gucer, Vasfi; Legmar, Guillaume; Standau, Markus; Thompson, Daniel; Vollmar, Christopher; Westphal, Axel (IBM Redbooks, 2023)
IBM Storage Sentinel is a cyber resiliency solution for SAP HANA, Oracle, and Epic healthcare systems, designed to help organizations enhance ransomware detection and incident recovery. IBM Storage Sentinel automates the creation of immutable backup copies of your data, then uses machine learning to detect signs of possible corruption and generate forensic reports that help you quickly diagnose and identify the source of the attack. Because IBM Storage Sentinel can intelligently isolate infected backups, your organization can identify the most recent verified and validated backup copies, greatly accelerating your time to recovery. This IBM Redbooks publication explains how to implement a cyber resiliency solution for SAP HANA, Oracle, and Epic healthcare systems using IBM Storage Sentinel and IBM Storage Safeguarded Copy. Target audience of this document is cyber security and storage specialists.
Keywords: Cyber intelligence (Computer security); Computer networks -- Security measures; Internet -- Security measures; Surveillance des menaces informatiques; Réseaux d'ordinateurs; Sécurité; Mesures; Internet; Sécurité; Mesures; Computer networks; Security measures; Internet; Security measures